C‐Src drives intestinal regeneration and transformation. (30th April 2014) - Cordero, Julia B; Ridgway, Rachel A; Valeri, Nicola; Nixon, Colin; Frame, Margaret C; Muller, William J; Vidal, Marcos; Sansom, Owen J
Abstract The non‐receptor tyrosine kinase c‐Src, hereafter referred to as Src, is overexpressed or activated in multiple human malignancies. There has been much speculation about the functional role of Src in colorectal cancer (CRC), with Src amplification and potential activating mutations in up to 20% of the human tumours, although this has never been addressed due to multiple redundant family members. Here, we have used the adult Drosophila and mouse intestinal epithelium as paradigms to define a role for Src during tissue homeostasis, damage‐induced regeneration and hyperplasia. Through genetic gain and loss of function experiments, we demonstrate that Src is necessary and sufficient to drive intestinal stem cell (ISC) proliferation during tissue self‐renewal, regeneration and tumourigenesis. Surprisingly, Src plays a non‐redundant role in the mouse intestine, which cannot be substituted by the other family kinases Fyn and Yes. Mechanistically, we show that Src drives ISC proliferation through upregulation of EGFR and activation of Ras/MAPK and Stat3 signalling. Therefore, we demonstrate a novel essential role for Src in intestinal stem/progenitor cell proliferation and tumourigenesis initiation in vivo.